Mapping Scientific Outputs in the Field of Social Network Applications to Libraries and Information Centers - Mahdi Mohammadi; Hamadeh Almasi Rad; Jafar Ebadollah Amoughin; Zeynab Siami (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2022)
Objective: This study aimed to draw a scientific map and analyze the clusters of research published in the field of social network applications to libraries and information centers using documents indexed in Web of Science.Methods: This research is applied research conducted using content analysis and a descriptive-analytical approach. The statistical population is 307 publications in the field of social networks in libraries and information centers, indexed in Web of Science between 2016 and 2020. The data collection tool is a researcher-made checklist. Excel and scientometric softwares were used to analyze the data.Results: The results showed that the keywords of social media, academic libraries, social network, and social network analysis have the highest frequency. The findings also indicated that the subject area of social networks includes nine clusters; the main cluster is related to the second cluster, which is mainly associated with social media and consists of 13 keywords.Conclusions: The results of the research show that social networks had a special role and position in the field of library and information sciencein 2018. The number of publications in this field in 2020 is far less than the previous years and the number of published works in this year has been decreasing. According to the research done on social networks and their various aspects, much research has been conducted, and all its aspects have been investigated. However, the investigation of research in this area with an emphasis on its application in libraries and information centers has not been done, and the present study can familiarize researchers with the conducted research and guide them to conduct applied research to fill the existing gaps.